Localisation and direction of mitral regurgitant flow in mitral orifice studied with combined use of ultrasonic pulsed Doppler technique and two dimensional echocardiography. Issue 5 (November 1982) - Miyatake, K; Nimura, Y; Sakakibara, H; Kinoshita, N; Okamoto, M; Nagata, S; Kawazoe, K; Fujita, T
Abstract : Regurgitant flow was analysed in 40 cases of mitral regurgitation, using combined ultrasonic pulsed Doppler technique and two dimensional echocardiography. Abnormal Doppler signals indicative of mitral regurgitant flow were detected in reference to the two dimensional image of the long axis view of the heart and the short axis view at the level of the mitral orifice. The overall direction of regurgitant flow into the left atrium was clearly seen in 28 of 40 cases, and the localisation of regurgitant flow in the mitral orifice in 38 cases. In cases with mitral valve prolapse of the anterior leaflet or posterior leaflet the regurgitant flow was directed posteriorly or anteriorly, respectively. The prolapse occurred at the anterolateral commissure or posteromedial commissure and resulted in regurgitant flow located near the anterolateral commissure or posteromedial commissure of the mitral orifice, respectively. In cases with rheumatic mitral regurgitation the regurgitant flow is usually towards the central portion of the left atrium and is sited in the mid-part of the orifice. The Doppler findings were consistent with left ventriculography and surgical findings. The ultrasonic pulsed Doppler technique combined with two dimensional echocardiography is useful for non-invasive analysis and preoperative assessment of mitral regurgitation.